HUBUNGAN KETERGANTUNGAN PROSES ANTARA PROSES SPLITTING DAN DISTILASI PADA INDUSTRI OLEOKIMIA - Muhammad Yusuf Ritonga (Jurnal Teknik Kimia USU, 2013)
The normal production yield target of a fatty acid distillated products (FADP) or DPOFA (Distilled Palm Oil Fatty Acid)’s fail to be achieved, and lead to do a particular analysis and study - to solve the problem in industrial scale. The DPOFA’s manufactured through degumming, splitting and distillation processs. The production yield’s improved in this study by using trial and error method. The improved splitting degree (98 % minimum) helped much better DPOFA production yield - come to be 93 % (normal target). There are strong processes interrelationship between splitting and distillation process.